Evaluation of the efficiency of some predators of aquatic insects as substitutes to disinsect the incomplete of mosquitoes (Culex pipiens molestus ForskalDiptera: Culicidae) - Makhlaf, Atallah Fahd; Khudair, Ghazwan Thamer (Arab Journal for Sciences and Research Publishing, 2016)
All vector control programs emphasize the use of biological control. Anisops sardea (Notonectidae: Hemiptera) and Orthetrum chrysostigma (Libellulidae: Odonata) were common in freshwater communities in Mosul. They were predators of wing-wing larvae. The effectiveness of predisposition, efficacy of research, Study on predators O. chrysostigma, A. sardea using the incomplete stages of mosquitoes Culex pipiens molestus and Chironomus ninevah in the laboratory. Backbones consumed 9.0, 8.0, 6.7 and 6.7 of the four larval ages respectively and 5.3 virgins within 24 hours while the mantis nestled at the same time 8.7 6.7, 6.3 and 5.3 larvae of the four ages respectively and 3.3 virgins. Both predators preferred the third and fourth stages when faced with all the incomplete stages of the prey. The co-existence and synergy between predators O.chrysostigma and A.sardea increased the effectiveness of predation by 17% together. The number of prey consumed per day increased with increasing density in the predators' Search coefficient for both predators. The Orthetrum chrysostigma preferred the Hamoush larvae to the mosquito larvae while the  Anisops sardea preferred mosquito larvae to the Hamoush  larvae significantly.
Keywords: Culex pipens molestus; Anisopssardea; Orethtrumy; Ministry of Education; University of Mosul; predation; Biological control